THE USE OF COOPERATIVE LEARNING IN DEVELOPING STUDENTS' SPEAKING SKILLS:(A Mixed-Method Study at a Vocational High School in Cimahi) - Gustary, Devian Try (2016)
The teaching of speaking skills has become increasingly important in the English as a second or foreign language (ESL/EFL) context. Nevertheless, lack of motivation, getting students to speak, and use of first language are the biggest challenges in developing speaking skills. Additionally, teachers' dominance to talk in the classroom makes students become passive listeners. An alternative way of teaching for promoting students' speaking skills can be found in cooperative learning since it provides the opportunity to practice English and create active learning atmosphere for students to learn by themselves and from their peers. However, little attention has been paid to conduct cooperative learning in developing speaking skills of secondary level especially in Indonesian context. Thus, this study aims to investigate how the techniques of cooperative learning develop students' speaking skills and to find out benefits and challenges during the implementation of cooperative learning in one vocational school in Cimahi. The study employed mixed method design since both qualitative and quantitative data were collected. The data were obtained from classroom observations, questionnaires, semi structured interview and students' spoken test. The results showed that despite some limitations; (1) the implementation of cooperative learning elements in each technique had facilitated students to develop their speaking skills especially in terms of their fluency, accuracy and confidence. This finding was also supported by statistical calculation using pair T-test which showed that there was a difference in the students' speaking skills after they learned with cooperative learning techniques; (2) the benefits of cooperative learning techniques involved three main categories which were achievement, interpersonal relationships, psychological health and social competence;(3) nevertheless, time constraint leads to inadequate time to practice students' speaking especially in terms of their grammar, to proper implementation the five elements of cooperative learning, and to teaching social skills; (4) thus, it is suggested that the future researchers can conduct the similar study in more meetings to make sure that the elements of cooperative learning and the social skills needed are applied in the teaching and learning process and to ensure that the students have more practice in the target language. Keywords: Cooperative Learning, Speaking skills, EFL